2008
DOI: 10.3141/2044-02
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Procedure for Performance-Based Road Maintenance Evaluations

Abstract: system (1,2). This initiative calls for performance-based work, in which a desired outcome is specified rather than materials or techniques to be used by the contractors to maintain the asset items. In performance-based contracts, road administrators define performance measures that specify the minimum acceptable condition at which the asset items should be maintained. To ensure that contractors maintain the asset items according to these measures, road administrators must design and implement a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…One classic sampling method in transportation maintenance management is stratified sampling as it balances trade‐offs between inspection costs and sampling accuracy (Adams and Winkelman, ; De la Garza et al., ; Medina et al., ). De la Garza et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One classic sampling method in transportation maintenance management is stratified sampling as it balances trade‐offs between inspection costs and sampling accuracy (Adams and Winkelman, ; De la Garza et al., ; Medina et al., ). De la Garza et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De la Garza et al. () proposed a stratified sampling method for road maintenance evaluation. The stratification criteria include geographical location, weather variation, urban and rural setting, and traffic volume.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although this approach for determining sample size is relatively simple, it may not be justified statistically. In order to correctly define a sampling procedure, de la Garza, Pinero, and Ozbek (2008) suggested that the characteristics of the 'population, sample units, asset items within each sample unit, and acceptable quality levels must be understood'. Several statistical methods have been proposed in the literature for computing the number of sample units needed to be inspected (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…sample size). For a given precision and confidence level, the necessary sample size is determined as a function of size of the network, estimates of the population variance, desired precision and desired confidence level (de la Garza et al, 2008;Kardian & Woodward, 1990;Medina, Haghani, & Harris, 2009). This approach for determining sample size is founded on statistical principles and is adopted in this paper.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Appropriate control procedures as well as penalties for non-compliance have to be well Researchers (De la Garza et al, 2009, Pin˜ero, 2003, Pin˜ero and De la Garza, 2004, de la Garza et al 2008de la Garza et al , 2009 identified five components in order to develop a framework for monitoring performance in PBC. These five components can be applied as guidelines to establish a performance monitoring system for PBC in Abu Dhabi.…”
Section: Performance Monitoringmentioning
confidence: 99%